Antifungal effects of essential oils on the preservation of historical monuments: A sustainable approach - Hatice Yıldız Acar; Hacer Bakır Sert (PLoS ONE, 2026)
This study investigates the antifungal properties of essential oils derived from plants in the Lamiaceae family for the preservation of historical structures affected by black microcolonial fungi in the Ancient City of Side, located in Southern Anatolia. Black microfungi, known for their role in the biodeterioration of cultural heritage, were isolated from corroded historical structures. The study specifically focused on essential oils extracted from Origanum majorana L., Origanum minutiflorum O. Schwarz & P.H. Davis, and Mentha longifolia L. subsp. typhoides (Brig.) Harley. The antifungal activity of these essential oils was evaluated under in vitro conditions at three concentrations (0.1%, 1%, and 3%). Microfungal cell counts were performed before and after the application of the essential oils. The results demonstrated a concentration-dependent antifungal effect, with higher concentrations (3%) showing the most significant inhibition of fungal growth. Essential oils from O. majorana , O. minutiflorum , and M. longifolia effectively suppressed the growth of Coniosporium , Sarcinomyces , and Phaeococcomyces species, which are major contributors to the biodeterioration of historical structures in the study area. These findings highlight the potential of essential oils as eco-friendly and sustainable antifungal agents for the conservation of cultural heritage. By mitigating black microfungal colonization, these natural compounds offer a promising alternative to synthetic biocides, aligning with the growing demand for environmentally friendly preservation methods. Further research is recommended to explore their long-term efficacy and practical applications in the field of cultural heritage conservation.